Comparative study of UHC implementation in Indonesia and Malaysia: Literature review - Rahim, Mohammad Afiff Bin; Rosyidah, Rosyidah; Hidayat, Muhammad Syamsu (Science Midwifery, 2025)
Universal Health Coverage Universal Health Coverage (UHC) is a key principle of an equitable health system, ensuring access to healthcare services without financial burden. Indonesia, with its National Health Insurance (JKN), and Malaysia, with its tax-based public healthcare system, have different approaches to implementation. This study compares the implementation of UHC in Indonesia and Malaysia, including the financing system, resource distribution, service coverage, and service quality. The study used a literature review with the PRISMA approach. From the total number of articles found in various databases, titles, abstracts, and inclusion-exclusion criteria were screened, leaving 15 relevant articles for analysis. Indonesia, through JKN, has covered a large portion of the population, but faces disparities in access, unequal distribution of healthcare workers, and high out-of-pocket costs for specialist services. Malaysia has near-universal coverage with subsidized public services and financial protection for poor households, although there is inequality between the public and private sectors. Indonesia needs to improve infrastructure, equitable distribution of healthcare workers, public education regarding active participation, and strengthened program management. Malaysia is advised to strengthen the integration of the public and private sectors and maintain progressive financing to reduce financial risks for poor households.